2018
DOI: 10.1038/s41598-018-30383-z
|View full text |Cite
|
Sign up to set email alerts
|

A single N1-methyladenosine on the large ribosomal subunit rRNA impacts locally its structure and the translation of key metabolic enzymes

Abstract: The entire chemical modification repertoire of yeast ribosomal RNAs and the enzymes responsible for it have recently been identified. Nonetheless, in most cases the precise roles played by these chemical modifications in ribosome structure, function and regulation remain totally unclear. Previously, we demonstrated that yeast Rrp8 methylates m1A645 of 25S rRNA in yeast. Here, using mung bean nuclease protection assays in combination with quantitative RP-HPLC and primer extension, we report that 25S/28S rRNA of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(26 citation statements)
references
References 57 publications
0
26
0
Order By: Relevance
“…In yeast abolition of a single base modification, i.e., m1A645 located on the LSU, leads to a change in the quantity of a subset of 18 proteins [ 127 ]. Comparison of the protein abundance with mRNA levels of each protein candidate showed that mRNA content did not correlate with protein content for some of the candidates.…”
Section: Impact Of Rrna Modifications On Ribosome-mediated Regulatmentioning
confidence: 99%
“…In yeast abolition of a single base modification, i.e., m1A645 located on the LSU, leads to a change in the quantity of a subset of 18 proteins [ 127 ]. Comparison of the protein abundance with mRNA levels of each protein candidate showed that mRNA content did not correlate with protein content for some of the candidates.…”
Section: Impact Of Rrna Modifications On Ribosome-mediated Regulatmentioning
confidence: 99%
“…The m 1 A modification in tRNAs was important for tRNA folding, stability, and tRNA-protein interaction [4952]. The m 1 A modification was also observed at several sites in rRNAs, which affect the tertiary structure of the ribosome and downstream gene translation [53, 54]. In contrast to non-coding RNAs, m 1 A modification has a relatively low abundance in mRNAs, with a potential function in regulating translation process [47].…”
Section: Resultsmentioning
confidence: 99%
“…m1A is found in the large subunit of the ribosome at position A1322 in 28S rRNA, and it is introduced by nucleomethylin (NML). It affects the local structure of the ribosome, promoting proper conformation of the 60S and ultimately translation [ 71 , 72 ]. Two different methods for the detection of m1A have been described and they rely on the ability of m1A to stall transcription [ 71 , 73 , 74 , 75 ].…”
Section: Ribosomal Rna Modifications and Their Biological Functionmentioning
confidence: 99%